Hybrid Control Using Adaptive Fuzzy Sliding Mode Control of Doubly Fed Induction Generator for Wind Energy Conversion System - Cherifi, Djamila; Miloud, Yahia (Periodica polytechnica. Electrical engineering and computer science, 2020)
In this paper, we are interested in the development of a robust control of active and reactive power for a Doubly Fed Induction Generator for variable speed wind energy using hybrid control by Adaptive Fuzzy logic and Sliding Mode Controller (AFSMC). This type of control is introduced to avoid the major disadvantage of variable structures systems which is the chattering phenomenon. Using the variable structure is to ensure the high dynamic of convergence and the robustness towards parametric variations and disturbances. Whereas the fuzzy control is introduced here in order to remove residual vibrations in high frequencies. Simulation results show that the proposed control strategy gives better results.